Healing music in the Asháninka communities of the Tambo river basin - Fabián Arias, Beatriz Anastacia (2021)
The objective of the research was to determine the main characteristics of healing music in the Ashaninka communities of the Tambo river basin, district of Río Tambo, province of Satipo, in the central jungle of Junín. The research is qualitative, applied type, exploratory level, ethnographic method, non-experimental design. The instruments used were the interview guide and the observation guide; the epistemology that supports the research is the cultural-historical theory of Lev Semionovich Vigotsky. The representative sample consisted of 30 participants. The main characteristics found were ritual, medicinal, aesthetic, performed with traditional musical instruments and communitarian. It is concluded that the music is ritual because it is religious and the forest is a temple of spirits. It is medicinal, because it heals psychosomatic illnesses. It is aesthetic because the sheripiari is a composer and spiritual guide. It is interpreted with traditional musical instruments using their own codes. It is communitarian, because it is festive in the community.